Cerebral perfusion differences in the visual cortex and fusiform subregions across the psychosis spectrum - Sritharan, Jothini; Zeng, Victor; Petr, Jan; Mutsaerts, Henk-Jan; Hoang, Dung; Bolo, Nicolas R.; Ivleva, Elena I.; Dai, Weiying; Gershon, Elliot S.; Keedy, Sarah K.; Parker, David A.; Trotti, Rebekah L.; et al. (Frontiers in Psychiatry, 2025)
BackgroundApproximately 50% of individuals with psychosis spectrum disorders (PSD) experience visual hallucinations and deficits in visual processing. Cerebral blood flow (CBF) alterations have been identified in the occipital lobe (OL) and fusiform gyrus (FG) in PSD. However, prior studies neither report on cytoarchitectonic subregions of the OL or FG, nor their correlations with cognition. Moreover, perfusion differences across neurobiologically defined psychosis Biotypes in these regions are not investigated yet.MethodsExploreASL and FreeSurfer were used to extract perfusion measures from pseudo-continuous arterial spin labeling scans of visual (hOc1-hOc3v, middle temporal area (MT)) and fusiform (FG2-FG4) subregions in 122 bipolar disorder with psychosis (BP), 179 schizoaffective disorder (SAD), 203 schizophrenia (SZ), and 350 healthy controls (NC), as well as psychosis Biotypes (BT1-3). The data was adjusted for scanner effects using ComBat. Analyses were co-varied for total gray matter CBF. We used R to perform statistical comparisons across PSD and NC and across Biotypes. Partial Spearman correlation was performed between CBF and cognitive measures. Benjamini & Hochberg correction was used to correct for multiple comparisons.ResultsPSD exhibited greater perfusion in MT and FG2 compared to NC. Perfusion significantly differed across psychosis Biotypes in hOc1 but not across diagnostic groups. Higher MT and FG4 perfusion in PSD were associated with worse overall cognitive performance.ConclusionsVisual and fusiform subregions demonstrate significant perfusion alterations which may indicate neurovascular deficits in PSD. Moreover, these perfusion alterations may contribute to cognitive impairments and visual abnormalities in psychosis.